The politics of autonomy : Indian experiences - Samāddāra, Raṇabīra (Sage Publications, 2005)
This volume tells us that a critical inquiry into the idea of autonomy suggests that the politics of the future will be the politics of autonomies: an engagement that combines notions like self-government, womens̀ autonomy, devolution of power, the rights of minorities, greater popular access to resources, and legal pluralism, and where different autonomies must learn to negotiate and co-exist. Viewing democratic theory through the lens of autonomy, the contributors:. - argue that autonomy has to be an essential ingredient in the building of post-colonial democracies, not merely a residual mea.